DAMPAK PERUBAHAN IKLIM TERHADAP PRODUKSI, PENDAPATAN DAN KETAHANAN PANGAN RUMAHTANGGA PETANI KELAPA DI PROVINSI SULAWESI UTARA - , RONALD TIMBUL PARDAMEAN HUTAPEA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The coconut plantation in Nort Sulawesi reachs 273.194 ha dan 42,72% of the population depend on the coconut farm. Climate is an environmental factor that affects the coconut production and impacts on the coconut farmerâs income and levels of household food security of the coconut farmers. The purpose of this study is to know : 1) the impact of climate change on the production of coconut crops in Nort Sulawesi Province, 2) factors that affect the productivity of coconut farm, 3) factors that affect the level of technical efficiency, 4) factors that affects the coconut farm income, and 5) a level of household food security of coconut farmers, and factors that influence. The research was conducted in Province of North Sulawesi covering North Minahasa Regency, South Minahasa Regency and Bolaang Mongondouw Regency. Collecting simple random samples as much 50 households in each regency, so the total of samples in three regency is 150 households of coconut farmers. The analysis using the Ordinary Least Square Method (OLS) and a method of estimation of stochastic frontier model that was done through 2 steps, those are OLS model for estimate parameters of technology and production input by using Maximum Likelihood Estimation Method (MLE). Result of the research shows that the coconut production in North Sulawesi Province was influence by variables of amount of climate rainfall as much as 0,19% and the average of air temperature as much as 2,80%. The average value of technical efficiency level as much as 0,85%, allocative efficiency as much as 0,85%, and economic efficiency 0,72%. This indicates that the coconut farmers have managed their farming efficiently. Variables that influence the incresing of coconut production are a width of land, supply of labours, plant population and types of coconut seeds. Factor of the plant age decreases the coconut production 0,10%, and perception to the climat influence negatively to the coconut production. The coconut farming income increase significantly by increasing amount of wide area, plant population, pattern of planting, but decreasing by increasing of labour wage, cost of pesticide, cost of transportation, land status, and perception to climate. The level of food security of household of coconut farmers classified on food secure (44%), however it is still found food insecure households (8,67%). The household food security of coconut farmers increase by increasing of the coconut farmerâs income and others incomes, but the level decreases by increasing prices of rice, fish, eggs, vegetables, cooking oil, and electricity cost. The analysis result of climate change towards the production, income and food security shows that climate has a negative and significant impact on the production and farming revenues, but to the level of household food security of coconut farmers shows a negative and unreal influence